Special Weapons and Tactics Occupational-Specific Physical Assessments and Fitness Measures - Strader, Jessica (Int J Environ Res Public Health, 2020)
Specialist tactical response police are required to frequently perform physically demanding tasks at high-risk capability levels, emphasizing the need for optimal physical fitness in this population. The aim of this study was to investigate the relationships between select measures of physical fitness and performance on an occupational-specific physical assessment (OSPA). A retrospective analysis on 18 male specialist police candidates (age = 32.1 ± 5.04 yrs; height = 183.72 ± 5.79 cm; body mass = 89.44 ± 8.56 kg; body mass index (BMI) = 26.45 ± 1.58 kg/m(2)) was conducted. Data were comprised of anthropometric measures, assorted fitness measures and OSPA performance scores. A stepwise linear regression determined the influence of measured fitness parameters on OSPA performance. A regression featuring both the 1 RM military shoulder press and grip strength of the non-dominant hand was the most significant predictor of performance (adjusted r(2) = 0.565, p = 0.001). A separate model, exclusively using the 1 RM military shoulder press additionally predicted OSPA performance (adjusted r(2) = 0.240, p = 0.023). These results emphasize the importance of optimal upper-limb muscular strength and its impact on key occupational tasks in specialist police candidates.